Analisis Perilaku Investor Perspektif Gender Dalam Pengambilan Keputusan Investasi di Pasar Modal Studi Kasus GI BEI UNIM - Yuliasnita Verlandes; Agoes Hadi Purnomo; Nurdiana Fitri Isnaini (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
The capital market is a market for various long-term financial instruments that are transacted, either in the form of debt or own capital, which is one of the sources for obtaining funds or capital for national development financing. The capital market as one of the national economic instruments has an intermediary function to bridge between those who have funds and those who need funds. With regard to gender, between men and women have different perspectives with men. Differences in perspectives in viewing and responding to decision-making problems experienced by women are no exception in terms of making investment decisions. The results of the study stated that both men and women have the same tendency in investing. Furthermore, what determines decision making in investing in the capital market is the aspect of education, income, employment and age.